Imperial incarceration : detention without trial in the making of British colonial Africa - Lobban, Michael (Studies in legal history., 2021)
For nineteenth-century Britons, the rule of law stood at the heart of their constitutional culture, and guaranteed the right not to be imprisoned without trial. At the same time, in an expanding empire, the authorities made frequent resort to detention without trial to remove political leaders who stood in the way of imperial expansion. Such conduct raised difficult questions about Britain's commitment to the rule of law. Was it satisfied if the sovereign validated acts of naked power by legislative forms, or could imperial subjects claim the protection of Magna Carta and the common law tradition? In this pathbreaking book, Michael Lobban explores how these matters were debated from the liberal Cape, to the jurisdictional borderlands of West Africa, to the occupied territory of Egypt, and shows how and when the demands of power undermined the rule of law. This title is also available as Open Access on Cambridge Core.